Les ambiances des hydrocarbures - Tobias Etienne-Greenwood (Ambiances)
For a decade, the exploitation of the Vaca Muerta hydrocarbon formation in Argentina has brought its share of political and economic controversies as well as serious environmental damages. These transformations also have consequences on the sensitive experience of the project’s opponents. This article explores how the opponents to the project try to decipher the atmosphere that radiates from an industrial complex that makes it difficult to distinguish between the underground, the surface, and the surrounding air. It is this subterranean atmosphere that penetrates, swathes, and finally disturbs the worlds of everyday life that activists and inhabitants alike describe in their testimonies and practices. The analysis of these forms of ordinary criticism also makes it possible to highlight the importance of atmosphere when it comes to taking collective action against these extractive industries.